Safety and tolerability of a natural supplement containing glucosinolates, phytosterols and citrus flavonoids in adult women: a randomized phase I, placebo-controlled, multi-arm, double-blinded clinical trial - Villar-López, Martha (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.